Stiffness and Creep Properties of HRS-BC Powered by Palm Shell Gasification in Dryer Unit - Intan Devi Nataliasari; Sunu Herwi Pranolo; Florentina Pungky Pramesti; Ary Setyawan (Journal of Engineering and Technological Sciences, 2022)
Roads are infrastructure that is very important in supporting people’s daily lives. With the high growth rate of traffic, the traffic load will cause damage to the road pavement in the form of deformation (rutting) and fatigue. The performance of an HRS-BC asphalt mixture was investigated to determine the asphalt’s resistance to damage. HRS-BC asphalt mixture specimens were produced by a palm shell AMP and by a diesel AMP. The performance of the HRS-BC asphalt mixture was tested in the laboratory with indirect tensile stiffness modulus (ITSM) and dynamic creep test. The results showed that the HRS-BC asphalt mixture sample produced by the palm shell AMP had better stiffness than the HRS-BC asphalt mixture produced by the diesel AMP. Both the samples of the HRS-BC asphalt mixture produced by the palm shell AMP and by the diesel AMP were not deformed when given a standard load of 100 kPa and 3,600 load repetitions.